Intelligent buildings for energy consumption management - Bucur, I; Axinte, P; Pleşcan, C; Şerban, A (IOP Publishing, 2021)
The main concern of the paper is the energy consumption management, in relation to the advantages and disadvantages of an intelligent building. The building sector consumes about one third of primary energy. An intelligent use of energy could have an impact on the energy consumption and cost. Energy management is the process of controlling, conserving and monitoring the energy in a building or recently in a home. With the use of sensors, all systems are connected and useful data is gathered to improve the building’s efficiency. Intelligent building design is the future of building and building services sector. Enhancing energy preservation strategies and using sustainable design approaches are necessary in developing intelligent buildings. This implies a more effective approach to reaching the green goals, and it also implies financial savings. Building an intelligent building involves a larger investment, but in the long run the usual expenses will decrease. National grid energy consumption will decrease with the use of renewable energy sources, such as solar or wind energy, if the energy is produced on site. In order to make a difference in the climate change, intelligent buildings depend on the non-fossil sources, which will affect the energy usage. Furthermore, an intelligent building will increase the comfort and productivity of its occupants, for either a workspace or a home.